Uma nova Expressão para a Variância da Velocidade Turbulenta Convectiva Derivada de um Modelo LES - Degrazia, Gervásio Annes (2013)
The aim of this study is to derive a new expression for the vertical turbulent velocity variance using LES data in a convective boundary layer.